Activation Energy Determination of Polyimide Film From Its Thermal Behaviour - Lakshmi, L. (Asian Journal of Chemistry, 2010)
This study deals the determination of activation energy of azo group containing polyimide film. Presence of azo group in the polymer enchances the reaction rate. The activation energy can be easily determined from the thermal degradation behaviour of polyimide film by four different method (a) Murray and White (b) Coats and Redfern (c) Doyles and (d) Freemans and Carrols method. The activation energy determined by different methods were compared.